Экономичный алгоритм вычисления телесного угла в численных методах решения задач математической физики - Калкаманов, С. А. (НТУ "ХПИ", 2004)
In the paper an economic algorithm of solid double layer potential that has corporeal angle geometrical sense computation is presented. Comparisons that show computing efficiency of the developed algorithm with known algorithms are presented
Keywords: методы граничных интегральных уравнений; сферический треугольник; формула Каньоли; аэрогидродинамика